Microbial succession and its effect on the formation of umami peptides during sufu fermentation - Mao, Jieqi; Zhou, Zhilei; Yang, Hongshun (Frontiers in Microbiology, 2023)
Sufu, a traditional Chinese fermented food, is famous for its unique flavor, especially umami. However, the formation mechanism of its umami peptides is still unclear. Here, we investigated the dynamic change of both umami peptides and microbial communities during sufu production. Based on peptidomic analysis, 9081 key differential peptides were identified, which mainly involved in amino acid transport and metabolism, peptidase activity and hydrolase activity. Twenty-six high-quality umami peptides with ascending trend were recognized by machine learning methods and Fuzzy c-means clustering. Then, through correlation analysis, five bacterial species (Enterococcus italicus, Leuconostoc citreum, L. mesenteroides, L. pseudomesenteroides, Tetragenococcus halophilus) and two fungi species (Cladosporium colombiae, Hannaella oryzae) were identified to be the core functional microorganisms for umami peptides formation. Functional annotation of five lactic acid bacteria indicated their important functions to be carbohydrate metabolism, amino acid metabolism and nucleotide metabolism, which proved their umami peptides production ability. Overall, our results enhanced the understanding of microbial communities and the formation mechanism of umami peptides in sufu, providing novel insights for quality control and flavor improvement of tofu products.